Kajian Model RME Berbasis Ethnomatematika untuk Memfasilitasi Kemampuan Berpikir Kritis Siswa - Singgih Utomo Aji (Publikasi Indonesia, 2023)
Mathematics is one of the sciences that can support and facilitate human life in almost all aspects. Therefore mathematics is a science that has an important role. The problem for studying mathematics is that it has an abstract nature so it is less desirable and is considered difficult to learn by students at school. This resulted in the results of Indonesian children's math ability being classified as low which were published by PISA. With this critical thinking ability, it is hoped that the math skills of Indonesian children can increase. Of course, this is the task of a teacher to design learning that can improve students' critical thinking skills to improve the mathematical abilities of Indonesian children and the learning design must overcome the abstractness of mathematics so that students can easily understand and learn mathematics. The RME (Realistic Mathematics Education) learning model is believed to be able to facilitate students' critical thinking skills thereby increasing students' mathematical abilities. In addition, RME can be combined with elevating the culture around students to attract students' interest while at the same time being able to overcome the abstractness of mathematics because learning is carried out in a real-life context. With a design like this it is expected that students can easily learn mathematics and can improve students' critical thinking skills. So that math skills can increase.